2012
DOI: 10.2223/jped.2241
|View full text |Cite
|
Sign up to set email alerts
|

Digestive tract neural control and gastrointestinal disorders in cerebral palsy

Abstract: Objectives: To examine the neural control of digestive tract and describe the main gastrointestinal disorders in cerebral palsy (CP), with attention to the importance of early diagnosis to an efficient interdisciplinary treatment.Sources: Systematic review of literature from 1997 to 2012 from Medline, Lilacs, Scielo, and Cochrane Library databases. The study included 70 papers, such as relevant reviews, observational studies, controlled trials, and prevalence studies. Qualitative studies were excluded. The key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 59 publications
2
28
0
13
Order By: Relevance
“…The damage is not progressive and it weakens in a variable way the coordination of the muscular action, resulting in the child's inability to maintain postures and to perform normal movements, being able, with the passage of time, to have changes in its clinical manifestations. It is classified by the body location of the neuromotor impairment, and the most common are tetraparesis, hemiparesis and paraparesis, and by type of tonus and posture alteration: athetoid, ataxic, hypotonic, spastic (corresponding to about 80% of cases) and mixed [1][2][3] . The major cause of CP is perinatal anoxia due to abnormal or prolonged labor.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The damage is not progressive and it weakens in a variable way the coordination of the muscular action, resulting in the child's inability to maintain postures and to perform normal movements, being able, with the passage of time, to have changes in its clinical manifestations. It is classified by the body location of the neuromotor impairment, and the most common are tetraparesis, hemiparesis and paraparesis, and by type of tonus and posture alteration: athetoid, ataxic, hypotonic, spastic (corresponding to about 80% of cases) and mixed [1][2][3] . The major cause of CP is perinatal anoxia due to abnormal or prolonged labor.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most frequently encountered difficulties are dysphagia for solids and liquids, regurgitations and vomiting, prolonged time to offer the meal and intestinal constipation. These manifestations are considered risk factors for eating disorders: by the motor alteration of the oropharyngeal dynamics; lack of understanding of the alimentary context and difficulty in the voluntary motor action of the oral phase, being able to alter the sequencing of the pharyngeal phase; and by the severity of pulmonary aspiration 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that feeding difficulties can interfere with the calorie intake required for the energy needs of children; thereby, it probably results in a decrease of the linear growth and a serious risk of malnutrition (9,19). Multiple etiologies such as motor disability, inadequate nutritional intake, and motor dysfunction were suggested as the factors causing malnutrition in children with CP (6)(7)(8). Inadequate nutrition may increase healthcare costs and limit functional mobility, particularly in children with severe motor impairments (21,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…As previously described (6)(7)(8), due to oral motor dysfunction, gastroesophageal reflux, and food refusal, the total caloric intake of children with CP is inadequate, which results in undernourishment and growth impairment. Neurological impairment along with malnutrition and low caloric intake may lead to slow linear growth and weight gain, which accompanies the lower height and weight in children with CP, compared with their healthy counterparts (9,10).…”
Section: Introductionmentioning
confidence: 92%